Оптимизация динамических процессов приводов технологических машин методом "Обобщённые безразмерные параметры" - Самидов, Халил Самид оглу; Ахадов, Анар Бейбала оглу (НТУ "ХПИ", 2016)
Работа посвящена оптимизации параметров динамических машин, в том числе металлорежущих станков. Предлагаемая методика позволяет при помощи несложных аналитических выражений установить связь между конструктивными, эксплуатационными параметрами и динамическими характеристиками проектируемой машины, прогнозировать ожидаемый уровень вибрации, создавать машины с заданными динамическими характеристиками и машины с наипучшими конструктивными параметрами.

The work is dedicated to the optimization of dynamic machine parameters, including machine tools. Compiled and simplified dynamic models of electromechanical drives of technological cars, taking into account the elastic damping properties of structures, characteristics of cutting forces and electromagnetic phenomena engines. They allow for the study of oscillations, motion stability and optimization of structural parameters of the machine. The method of "generalized dimensionless parameters" developed and implemented a method to optimize design parameters drives technological machinery, including pipe-91A38 machine, screw-cutting lathe 1K625 and three-mass dynamic models of cars for different purposes. The proposed method allows using a simple analytical expressions to establish a connection between the structural, operational parameters and dynamic characteristics of the machine designed to predict the expected vibration level, to create machines with specified dynamic characteristics of the machine and with the best design parameters.
Optimization of dynamic processes of technological machines drives by "Generalized dimensionless parameters"
Keywords: вибрация; конструкция; токарно-винторезный станок; электромеханические системы; vibration; construction